anonymous
  • anonymous
Solve by the substitution method 2x-10=-y 3x-y=0
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
anonymous
  • anonymous
Minus the 2x on the first equation to get -2x-y=-10 3x-y=0
anonymous
  • anonymous
Lets get rid of the y so multiply a - on the 1st equation to get 2x+y=10 3x-y=0 Then it will be 5x=10 Divide the 5 on both sides x=2 plug the 2 on one of the equations 3(2)-y=0 6-y=0 Subtract the 6 -y=-6 Divide the - y=6 So it is x=2 & y =6
anonymous
  • anonymous
Do you get it?

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
Hello?
anonymous
  • anonymous
Good use of the elimination method, but to answer the problem as posed, change the second equation to 3x=y and put it into the first equation 2x-10=-3x then 5x=10 then x=2 and y =6. Substitution method.
anonymous
  • anonymous
(x,y)=(2,6) (almost forgot to give the answer!!)

Looking for something else?

Not the answer you are looking for? Search for more explanations.